An interplay of the base excision repair and mismatch repair pathways in active DNA demethylation - Grin, Inga (Nucleic Acids Res, 2016)
Active DNA demethylation (ADDM) in mammals occurs via hydroxylation of 5-methylcytosine (5mC) by TET and/or deamination by AID/APOBEC family enzymes. The resulting 5mC derivatives are removed through the base excision repair (BER) pathway. At present, it is unclear how the cell manages to eliminate closely spaced 5mC residues whilst avoiding generation of toxic BER intermediates and whether alternative DNA repair pathways participate in ADDM. It has been shown that non-canonical DNA mismatch repair (ncMMR) can remove both alkylated and oxidized nucleotides from DNA. Here, a phagemid DNA containing oxidative base lesions and methylated sites are used to examine the involvement of various DNA repair pathways in ADDM in murine and human cell-free extracts. We demonstrate that, in addition to short-patch BER, 5-hydroxymethyluracil and uracil mispaired with guanine can be processed by ncMMR and long-patch BER with concomitant removal of distant 5mC residues. Furthermore, the presence of multiple mispairs in the same MMR nick/mismatch recognition region together with BER-mediated nick formation promotes proficient ncMMR resulting in the reactivation of an epigenetically silenced reporter gene in murine cells. These findings suggest cooperation between BER and ncMMR in the removal of multiple mismatches that might occur in mammalian cells during ADDM.